Libertarian Theories of the Corporate and Global Capitalism - Arnold, Denis G. (Journal of business ethics, 2003)
Libertarian theories of the normative core of the corporation hold in common the view that is the responsibility of publicity held corporations to return profits to shareholders within the bounds of certain moral side-constraints. Side-constraints may be either weak (grounded in the rules of the game) or strong (grounded in rights). This essay considers libertarian arguments regarding the normative core of the corporation in the context of global capitalism and in the light of actual corporate behavior. First, it is argued the weak side-constraints view is conceptually incoherent when applied in a global context. Second, it is argued that proponents of the libertarian strong side-constraints view lack an adequate theory of rights. Third, both the weak side-constraints view and the strong side-constraints view are shown to be unsatisfactory insofar as they fail to adequately address the coercive power of corporations. The main conclusion of this essay is that a viable libertarian theory of the corporation has yet to be articulated.